2009
DOI: 10.1007/s00455-009-9245-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dysphagia on Quality of Life in Ageing and Parkinson’s Disease as Measured by the Swallowing Quality of Life (SWAL-QOL) Questionnaire

Abstract: This prospective, cross-sectional study evaluated the impact of dysphagia on quality of life in healthy ageing and in subjects with Parkinson's disease (PD) using the Swallowing Quality of Life (SWAL-QOL) questionnaire. Sixteen healthy young adults (8 males, mean age = 25.1 years) and 16 healthy elders (8 males, mean age = 72.8 years) were recruited. Thirty-two subjects with idiopathic PD (mean age = 68.5 years) were recruited from a movement disorders clinic. The severity of PD was staged using the Hoehn and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(126 citation statements)
references
References 19 publications
6
114
0
6
Order By: Relevance
“…Our results, that indicate elevated scores in healthy elderly, corroborate a study developed to investigate the quality of life with the advance of age and with Parkinson's disease (25) , using SWAL-QOL. The authors concluded that there are no differences regarding the means presented by the healthy elderly and healthy young adults, that is, the normal aging process do not affect swallowing.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our results, that indicate elevated scores in healthy elderly, corroborate a study developed to investigate the quality of life with the advance of age and with Parkinson's disease (25) , using SWAL-QOL. The authors concluded that there are no differences regarding the means presented by the healthy elderly and healthy young adults, that is, the normal aging process do not affect swallowing.…”
Section: Discussionsupporting
confidence: 86%
“…The elderly, in general, did not report difficulties related to swallowing and/or eating. It is possible that mild symptoms such as casual coughs, chewing difficulty and secretions, are considered by them as part of the natural aging process, and for that reason, do not create great bothers and concerns, as an international study showed, in which the healthy elderly took part in the control group and also answered the SWAL-QOL protocol (25) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of dysphagia in PD requires specialized rehabilitation combining treatment strategies that maximize social functioning, minimize the swallowing burden on the patient, and improve mental health [35].…”
Section: Resultsmentioning
confidence: 99%
“…Both Keage et al 30 and Timmerman et al 29 recommend the validated 'Swallowing Quality of Life' (SWAL-QOL) questionnaire as a first preference 34 . SWAL-QOL has been used in swallowing studies for different patient groups as well as for the evaluation of therapeutic effects 18,35 .…”
Section: Introductionmentioning
confidence: 99%